Hepatitis E in a Canadian Traveller. (1995) - Akai, Peter S; Fonseca, Kevin; Horne, Duff; Ho, May
Abstract : Hepatitis E is clinically indistinguishable from hepatitis A and is caused by an enterically transmitted rna virus that is endemic in developing countries of Asia, Africa, the Middle East and North America. This report describes a Canadian traveller to Nepal, Thailand and India with one of the first confirmed cases of hepatitis E reported in Canada. Although this disease is usually self-limited with no known sequelae, it may produce fulminant hepatitis with a high case fatality rate in pregnancy. Diagnosis can be confirmed by serological tests. Apart from strict food and beverage hygiene, there are presently no prophylactic measures against this disease, and pregnant women in the third trimester should avoid travel to endemic areas.